Sports Administratorsâ€™ Health Watch for Young Athletesâ€™ Participation in Sports for Commercialization in Nigeria - Simon, Kayit; Owojaiye, Sunday Oni (NIU Journal of Social Sciences, 2019)
This research report â€œSports Administratorsâ€™ Health Watch for Young Athletesâ€™ Participation in Sports for Commercialization in Nigeriaâ€ was culled to exhume the modus operandi for catching sports athletes from secondary schools. The population for this research is five hundred (500) senior secondary school students randomly selected from twenty (20) SSS I students from Kwara and Kogi States. The instrument used for data collection was researchers structured questionnaire that consists of ten (10) items that has to do with psycho-social and physio-technical factors. The psycho-social factors deal with 5 items while the physio-technical factors deal with 5 items. Data gathered was done by the researchers and ten research assistants. The data analysis was done using t-test method. Based on the results of data analysis and the discussions, it was discovered that: act of hooliganism resulting to injuries and even death deterred students. Drug abuse; and techniques of curbing it. iii. Early sexual indulgence hinder students. Non-motivation of sports students. Based on the discoveries, it was recommended that: The Federal, State and Local Government should through the Sports Council in each state, monitor the athlete star hunt during inter-house athletic competitions in the secondary schools. Monetary awards of 50,000 to 100,000 must be attached to students that are record breakers. Keywords: Sport administrators, Health watch, Young athletes participation  and commercialisation